The Style of Hawthorne's Gaze : Regarding Subjectivity - Dolis, John, 1945- (Book collections on Project MUSE., 2014)
The Style of Hawthorne's Gaze is an unusual and insightful work that employs a combination of critical strategies drawn from art history, philosophy, psychoanalysis, and contemporary aesthetic and literary theory to explore Nathaniel Hawthorne's narrative technique and his unique vision of the world. Dolis studies Hawthorne's anti-technological and essentially Romantic view of the external world and examines the recurring phenomena of lighting, motion, aspectivity, fragmentation, and imagination as they relate to his descriptive techniques. Dolis sets the world of Hawtho.